Polymers of unidimentional coordination [M(sac)2(H2O)(pyz)]n, (M= Ni2+, Cu2+ and Zn2+, sac =saccharinate, pyz= pyrazine), spectroscopy and magnetic properties - Valle-Bourrouet, Grettel (2011)
Coordination polymers have been prepared by the hydrothermal reaction of M2+saccharinates (M = Ni, Cu and Zn) and pyrazine, pyz, in a ratio 1:1. The complexes of formula [M(sac)2(H2O)2pyz]n, M = Ni2+ and Zn2+ and [Cu(sac)2(H2O)pyz]n were characterized by spectroscopic methods and elemental analysis, magnetic measurements, single and powder x-ray diffraction. The compounds crystallize in the triclinic space group p-1. The zinc ion is octahedrally coordinated by two sac ions, two water and two pyrazine molecules. The copper ion is penta-coordinated in a distorted square pyramidal geometry with the pyrazine molecules in the axial position. The metal atoms are connected via pyrazine μ-N,N’-coordination and form linear chains, containing a network of hydrogen bonds between the chains, that build a 2D sheet structure.